Advanced oxidation processes for wet-process phosphoric acid: Enhanced phosphorus recovery and removal of organic matters - Zhou, Yuhe; Zheng, Guocan; Long, Youqin; Liu, Zuohua; Tao, Changyuan; Liu, Renlong (Hydrometallurgy, 2022)
Green and efficient phosphorus leaching from phosphate rock (PR) is the key to producing high-quality products and reducing energy consumption. Organic matters in the PR affect the efficiency of wet-process phosphoric acid production. In this study, advanced oxidation processes (AOPs) were employed to remove organic matters, thereby intensifying the acidolysis reaction of the PR. The characteristics, effects of reaction conditions on the leaching efficiency, and leaching reaction were systematically studied. Under the optimal reaction conditions with the H2O2 concentration of 0.04 mL/mL, reaction temperature of 70 °C, reaction time of 120 min, and particle size of −150 μm, a high leaching efficiency of 88.4% was achieved in the O3-H2O2 reaction (OHR) case. In addition, the total organic carbon content in the leach liquor is 12.2 mg/L, which is significantly decreased by 79.9%. This demonstrated the advantages of AOP systems in strengthening the efficient leaching of phosphorus as well as beneficial environmental impact. [Display omitted] •Advanced oxidation process methods were employed to enhance phosphorus recovery.•Leaching efficiency was improved by removing organic matters during the acidolysis.•Total organic carbon content in the leach liquor is remarkably decreased by 80%.